A Nest of LTR Retrotransposons Adjacent the Disease Resistance-Priming Gene NPR1 in Beta vulgaris L. U.S. Hybrid H20. (19th February 2009) - Kuykendall, David; Shao, Jonathan; Trimmer, Kenneth
Abstract : A nest of long terminal repeat (LTR) retrotransposons (RTRs), discovered by LTR_STRUC analysis, is near core genes encoding the NPR1 disease resistance-activating factor and a heat-shock-factor-(HSF-) like protein in sugarbeet hybrid US H20. SCHULTE, a 10 833 bp LTR retrotransposon, with 1372 bp LTRs that are 0.7% divergent, has two ORFs with unexpected introns but encoding a reverse transcriptase with rve and Rvt2 domains similar to Ty1/copia -type retrotransposons and a hypothetical protein. SCHULTE produced significant nucleotide BLAST alignments with repeat DNA elements from all four families of plants represented in the TIGR plant repeat database (PRD); the best nucleotide sequence alignment was to ToRTL1 in Lycopersicon esculentum . A second sugarbeet LTR retrotransposon, SCHMIDT, 11 565 bp in length, has 2561 bp LTRs that share 100% identity with each other and share 98-99% nucleotide sequence identity over 10% of their length with DRVs, a family of highly repetitive, relatively small DNA sequences that are widely dispersed over the sugarbeet genome. SCHMIDT encodes a complete gypsy -like polyprotein in a single ORF. Analysis using LTR_STRUC of an in silico deletion of both of the above two LTR retrotransposons found that SCHULTE and SCHMIDT had inserted within an older LTR retrotransposon, resulting in a nest that is only about 10 Kb upstream of NPR1 in sugarbeet hybrid US H20.